2016
DOI: 10.1097/bpo.0000000000000511
|View full text |Cite
|
Sign up to set email alerts
|

Intercondylar Notch Width as a Risk Factor for Medial Femoral Condyle Osteochondritis Dissecans in Skeletally Immature Patients

Abstract: Level III-case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“… 8 In a study by Chow et al, a narrower intercondylar notch width was implicated as a risk factor for juvenile OCD lesions. 12 They postulated that this anatomic risk factor might increase the likelihood for tibial eminence impingement and contribute to an OCD lesion. In a radiographic study of 103 knees using full-length standing radiographs, Jacobi et al found an association between medial condyle OCD and varus malalignment of the knee.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In a study by Chow et al, a narrower intercondylar notch width was implicated as a risk factor for juvenile OCD lesions. 12 They postulated that this anatomic risk factor might increase the likelihood for tibial eminence impingement and contribute to an OCD lesion. In a radiographic study of 103 knees using full-length standing radiographs, Jacobi et al found an association between medial condyle OCD and varus malalignment of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods of notch size measurements on imaging have been described. 2,[8][9][10] However, most methods have been used to study the relationship of notch size to ACL injury, and few have tried to reproduce arthroscopic measurements. Zeng et al 11 performed a meta-analysis of 16 studies assessing the correlation between intercondylar notch size and the risk of ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…From the standpoint of the mechanical axis of the leg, there was no significant evidence of the specific mechanical axis change accounting for MFC OCD, as shown in LFC OCD. 16 As an anatomic risk factor for MFC OCD, Chow et al 6 recently demonstrated that knees with MFC OCD lesions have significantly narrower intercondylar notch width compared with controls using MRI scans. This study proposed a new approach to investigate anatomic risk factors predisposing to MFC OCD lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This study proposed a new approach to investigate anatomic risk factors predisposing to MFC OCD lesions. 6 Thus, few concepts and findings have been introduced to unveil the etiological factor of MFC OCD; however, many things still remain unclear and have to be proven to elucidate the cause of MFC OCD.…”
Section: Discussionmentioning
confidence: 99%